British Jacobin politics, desires, and aftermaths : seditious hearts - Epstein, James; Karr, David, 1963- (New York, NY : Routledge, 2021)
"This book explores the hopes, desires, and imagined futures which characterized British radicalism in the 1790s, and the resurfacing of this sense of possibility in the following decades. The articulation of "Jacobin" sentiments reflected the emotional investments of men and women inspired by the French Revolution and committed to political transformation. The authors emphasize the performative aspects of political culture, and the spaces in which mobilization and expression occurred - including the club room, tavern, coffeehouse, street, outdoor meeting, theater, chapel, courtroom, prison, and convict ship. America, imagined as a site of republican citizenship, and New South Wales, experienced as a space of political exile, widened the scope of radical dreaming. Part One focuses on the political culture forged under the shifting influence of the French Revolution. Part Two explores the afterlives of British Jacobinism in the year 1817, in early Chartist memorialization of the Scottish "martyrs" of 1794, and in the writings of E. P. Thompson. The relationship between popular radicals and the Romantics is a theme pursued in several chapters; a dialogue is sustained across the disciplinary boundaries of British history and literary studies. The volume captures the revolutionary decade's effervescent yearning, and its unruly persistence in later years"--
Playing at revolution: British "Jacobin" performance -- Everyday life and everyday sedition: situating radical identities -- "Thoughts that flash like lightning": Thomas Holcroft and radical theater -- "Equality and no king": sociability and sedition -- Writing America from Newgate Prison, 1795 -- 1817: return of the suppressed -- "The embers of expiring sedition": Maurice Margarot, the Scottish martyrs monument, and radical memory across the South Pacific -- Among the Romantics: E.P. Thompson and the poetics of disenchantment.
OCLC-licensed vendor bibliographic record.
Keywords: Political culture -- Great Britain -- History -- 18th century; Political culture -- Great Britain -- History -- 19th century; Politics and literature -- Great Britain -- History -- 18th century; Politics and literature -- Great Britain -- History -- 19th century; Radicalism -- Great Britain -- History -- 18th century; Radicalism -- Great Britain -- History -- 19th century; Great Britain -- Politics and government -- 1789-1820.; France -- History -- Revolution, 1789-1799 -- Influence; HISTORY / Europe / Great Britain; HISTORY / Europe / General; HISTORY / Europe / Western